Sustainability in Agave tequilana weber farming: A life cycle assessment - García-Alcaraz, Jorge Luis; Blanco Fernandez, Julio; Martínez Cámara, Eduardo (2024)
https://onlinelibrary.wiley.com/doi/10.1002/sd.3146